2021
DOI: 10.31234/osf.io/qejxv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Collective Emotions during the COVID-19 Outbreak

Abstract: The COVID-19 pandemic has exposed the world's population to sudden challenges that elicited strong emotional reactions. Although investigations of responses to tragic one-off events exist, studies on the evolution of collective emotions during a pandemic are missing. We analyzed the digital traces of emotional expressions in tweets during five weeks after the start of outbreaks in 18 countries and six different languages. We observed an early strong upsurge of anxiety-related terms in all countries, which was … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…These results are robust when considering autocorrelation and heteroskedasticity for all cases except for the last case of dictionary-based positive emotions. The case of dictionary-based anxiety also shows some signs of non-stationarity due to the large spike in the time series at the onset of the pandemic, as already reported with similar methods 27 , but results are still comparable when using robust estimators that consider outliers and in permutation tests (see SI for more details). Signals measured with the supervised method are comparable to the dictionary-based method for sadness and anxiety, but for the case of the emotion happy in YouGov, the supervised method gives significantly stronger positive correlations than the dictionary-based method in both the historical and prediction periods.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…These results are robust when considering autocorrelation and heteroskedasticity for all cases except for the last case of dictionary-based positive emotions. The case of dictionary-based anxiety also shows some signs of non-stationarity due to the large spike in the time series at the onset of the pandemic, as already reported with similar methods 27 , but results are still comparable when using robust estimators that consider outliers and in permutation tests (see SI for more details). Signals measured with the supervised method are comparable to the dictionary-based method for sadness and anxiety, but for the case of the emotion happy in YouGov, the supervised method gives significantly stronger positive correlations than the dictionary-based method in both the historical and prediction periods.…”
supporting
confidence: 74%
“…Following our pre-registration (https://aspredicted.org/blind.php?x=r89nv2), we analyzed the text of tweets using the anxiety, sadness, and positive affect dictionaries of LIWC through Brandwatch slightly adapted as in our previous work 27 . This way, we obtain a daily count of tweets within the sample that contain at least one emotional term, which we then average over weekly windows aligned with the YouGov survey.…”
Section: Methodsmentioning
confidence: 99%
“…Data analysis was done in R Version 3.6.1 (R Core Team, 2018), using the packages from the Tidyverse (Wickham et al, 2019), as well as lme4, scales, cowplot, ggrepel, and gridExtra (Auguie, 2017; Bates et al, 2015; Slowikowski, 2019; Wickham & Seidel, 2019; Wilke, 2019). All R code and data are available at https://osf.io/736kc/ (Metzler et al, 2021). Only the machine learning analysis for the robustness check was done in Python Version 3.9.2, using packages Transformers (4.5.1) and Torch (1.8.1+cu102).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, using metaphors as an analytic tool, Stanley et al (2021) have demonstrated that emotional experiences of COVID-19 converged around several deeply held negative emotions: (a) grief, (b) disgust, (c) anger and (d) fear. Meanwhile, Metzler et al (2021) analysed tweets from 18 countries during the first 5 weeks of the outbreak and observed a strong early upsurge in anxiety-related terms. Further, sadness terms rose and anger terms decreased around 2 weeks later as social distancing measures were implemented.…”
Section: Experiencing Emotion Within Diary-based Methods – a Worked E...mentioning
confidence: 99%